Characteristics of the mentor in surgery and its contribution in the education of the future: Características del mentor en cirugía y su contribución en la educación del futuro - Córdova-Aguilar, Alberto (2021)
Mentoring in surgery is the art of guiding a future surgeon toward specific academic and professional goals that are likely to determine career success. This mentoring requires a solid mentor-resident relationship and a mentor with certain characteristics such as: research productivity, understanding of pedagogy and the application of educational technology. The mentor in surgery is in charge of properly channeling the resident's various clinical-surgical experiences to achieve meaningful learning; likewise, experience and motivation are the main characteristics of a good mentor. The availability of the mentor is essential to foster a solid mentor-resident relationship, in order to achieve the academic and professional success of the future specialist; using not only theoretical-practical methods, but also the use of educational technology that will allow the maximum development of the mentee